Study on safety evaluation and design method of union joint thread for Ultra-high pressure fracturing manifold. (November 2022) - Dong, Liangliang; Xie, Xutao; Zhu, Xiaohua; Wang, Shiqiang; He, Sha
Highlights: A method for calculating the fatigue life of threaded joint with multi-axis fatigue. A method for optimizing threaded joint. Simulated the fatigue life analysis of a threaded joint subjected to 140MPa ultra-high pressure. Vibration fatigue is the key factor affecting fatigue fracture of the union joint thread. Abstract: Ultra-high pressure fracturing technology has become more and more important in China's deep Shale Gas extraction. In recent years, fracturing manifold failure accidents have happened frequently and service life has shortened drastically. There are more than 94% of failure accidents that are caused by vibration fatigue of the union joint. In this paper, it was established as a 3d finite element model of the union joint based on finite element theory and fatigue theory. The author proposed a safety evaluation method based on fatigue life, and compared it with that based on strength. The results show that vibration is the key factor affecting fatigue life, and the fatigue life-based safety evaluation method is more suitable to describe the union joint safety. Therefore, set fatigue life as optimization goal and the key parameters of the union joint thread are optimized by orthogonal optimization method. The optimal results are obtained from the study range, namely that the thread turns 8, the pitch is 10.47 mm, the bearing surface angle is 24.5°, and the guide surface angle is 24.5°. In comparison to the initial union joint, the fatigue life of the optimized union joint is increased by two orders of magnitude. These studies improve the fatigue performance of the union joint and have important guiding significance for improving the safety evaluation level of the fracturing manifold system in this paper.